PERAN WORK LIFE BALANCE DALAM MEMEDIASI HUBUNGAN BEBAN KERJA, DUKUNGAN SOSIAL, PENGHARGAAN, DAN BURNOUT PADA PEGAWAI BANK NAGARI - Felicia Citra Wibawa; Elfiswandi; Lusiana (Halu Oleo University, 2025)
This study aims to examine the influence of workload, social support, and rewards on burnout mediated by work-life balance. A quantitative approach with hypothesis testing techniques was used in this study. There were 95 samples with a judgmental sampling technique and using the Slovin formula, which represented Bank Nagari employees in West Sumatra Province. Data were collected through distributing questionnaires online and processed using SmartPLS 4.0 software with structural equation modelling techniques. The results showed that workload, social support, and rewards each had a significant effect on work-life balance. Workload, social support, rewards, and work-life balance each have a significant effect on burnout. The effect of workload, social support, and rewards on burnout through the mediation of work-life balance was found to be significant. The implications of the study emphasise the importance of maintaining employee welfare by paying attention to physical and emotional conditions in banking institutions in order to provide the best service for customers.